Pengaruh Motivasi Intrinsik, Budaya Organisasi, Dan Pengalaman Kerja Terhadap Kinerja Karyawan CV Bhakti Astawira Sejahtera Kabupaten Kulon Progo - Ramadhanti, Ardita Puri; Kurniawan, Ignatius Soni; Lysander, Mohammad Ahyar Syafwan (Gorontalo State University, 2026)
Increasing business competition drives organizations to optimize the quality of human resources to achieve company objectives effectively. This study aims to analyze the effects of intrinsic motivation, organizational culture, and work experience on employee performance at CV Bhakti Astawira Sejahtera in Kulon Progo Regency. The research employed a quantitative approach using a survey method with a saturated sampling technique involving all 53 employees. Data were collected through Likert-scale questionnaires and analyzed using the SEM-PLS method, including tests of validity, reliability, model fit, coefficient of determination, and hypotheses. The results indicate that intrinsic motivation and work experience significantly influence employee performance, while organizational culture shows no significant effect. Collectively, the three variables explain 55.8% of the variation in employee performance. The novelty of this study lies in identifying intrinsic motivation and work experience as compensatory factors for weak organizational culture internalization in medium-sized firms.